2022
DOI: 10.1155/2022/5245620
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus mitis/oralis Corneal Ulcer in a Patient with Severe Rheumatoid Arthritis: An Unusual Route

Abstract: Purpose. To report a case of Streptococcus mitis oralis (S. mitis/oralis) corneal ulcer in a patient with a possible preventable cause. Methods. Cultures were obtained from a 64-year-old woman with a 3.5   mm × 5   mm corneal ulcer with hypopyon in the left eye. Results. Culture rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Artificial tears are used to relieve dry eye symptoms and improve corneal epithelial healing. It is rare for keratitis to be specifically associated with contaminated artificial tears, although 1 case of Streptococcus mitis keratitis was attributed to a patient with rheumatoid arthritis biting the tops of her artificial tears bottles . The CDC recently reported that 55 patients in 12 states developed MDR P aeruginosa keratitis potentially associated with EzriCare artificial tear use with outcomes including permanent blindness, hospitalization, and death due to systemic infection .…”
mentioning
confidence: 99%
“…Artificial tears are used to relieve dry eye symptoms and improve corneal epithelial healing. It is rare for keratitis to be specifically associated with contaminated artificial tears, although 1 case of Streptococcus mitis keratitis was attributed to a patient with rheumatoid arthritis biting the tops of her artificial tears bottles . The CDC recently reported that 55 patients in 12 states developed MDR P aeruginosa keratitis potentially associated with EzriCare artificial tear use with outcomes including permanent blindness, hospitalization, and death due to systemic infection .…”
mentioning
confidence: 99%